2023
DOI: 10.1111/cdev.14036
|View full text |Cite
|
Sign up to set email alerts
|

Young children's adaptive partner choice in cooperation and competition contexts

Sebastian Grueneisen,
Georgina Török,
Anushari Wathiyage Don
et al.

Abstract: Choosing adequate partners is essential for cooperation, but how children calibrate their partner choice to specific social challenges is unknown. In two experiments, 4‐ to 7‐year‐olds (N = 189, 49% girls, mostly White, data collection: 03.2021–09.2022) were presented with partners in possession of different positive qualities. Children then recruited partners for hypothetical tasks that differed with respect to the quality necessary for success. Children and the selected partner either worked together toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…In light of the fact that the older children in Experiment 1 performed well, the poor performance of the older children who took part in Experiment 2 raises questions. Ample studies have demonstrated that from four-years of age, children are capable of flexibly switching between models that show expertise in different domains in the cooperative context (e.g., Hermes et al, 2016) and in a very recent study, 5-6-year-olds avoided competent players in domain-relevant competitive tasks (Grueneisen et al, 2023). Yet in the present experiment, not even the oldest children (seven-yearolds) performed well in the cooperative context.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…In light of the fact that the older children in Experiment 1 performed well, the poor performance of the older children who took part in Experiment 2 raises questions. Ample studies have demonstrated that from four-years of age, children are capable of flexibly switching between models that show expertise in different domains in the cooperative context (e.g., Hermes et al, 2016) and in a very recent study, 5-6-year-olds avoided competent players in domain-relevant competitive tasks (Grueneisen et al, 2023). Yet in the present experiment, not even the oldest children (seven-yearolds) performed well in the cooperative context.…”
Section: Resultscontrasting
confidence: 55%
“…Rather than the children themselves feeling true emotion after winning or losing a game, they watch their character display the appropriate response. Interestingly, a recent study (Grueneisen et al, 2023) obtained similar results, with 6-7-year-olds but not 4-5-year-olds choosing co-action partners in adaptive context-specific ways, in an online experiment.…”
Section: Resultsmentioning
confidence: 52%
“…One reported change at this age range is that only children older than 8 years can verbally explain the self-reputational consequences of various rule violations (Banerjee et al, 2010), though already 5-year-olds show evidence for behavioural reputation management (Engelmann et al, 2012). Similarly, although younger children may understand aspects of joint commitment (Gräfenhain et al, 2009) and how to choose the most cooperative partner (Grueneisen et al, 2023), the ability to understand promises, how to form commitments and the consequences they entail manifests only at 9 to 10 years of age (Maas and Abbeduto, 2001; Mant and Perner, 1988). Thus, it appears that the advanced use of language, in this case, to express shared intentionality, could be the key cognitive mechanism promoting successful cooperation in the egg hunt from 10 years onwards.…”
Section: Discussionmentioning
confidence: 99%